Some issues related to the concept and methods of theft - Simonyan, Tigran (Bulletin of Yerevan University C: Jurisprudence, 2024)
Theft is at the core of property crimes; it is their central element. From this perspective, studying the concept and methods of committing this crime is always relevant and important. This article examines some problematic issues related to the concept of theft and its methods as defined by the new (current) Criminal Code of the Republic of Armenia. These issues are quite problematic, and clarifying them, as well as proposing further legislative improvements, is both relevant and necessary. The purpose of the article is to investigate the existing problems with the legislative definition of theft, its completion, and the methods of committing theft, and to provide proposals for improving legislative formulations that require immediate resolution. The article discusses, in separate paragraphs, the concept of theft, some peculiarities of its definitions, as well as problems with legislative formulations and the qualification of methods of theft. The object of the study was examined using both general scientific and specialized methods, such as dogmatic, comparative-legal, and logical analysis. As a result of the research, legislative proposals are presented for the formulation of the concept of theft and methods of committing it, aimed at improving criminal law norms, specifically: In the context of ensuring a unified legislative logic, the concept of theft should either be revised to include references to mercenary motives or completely abandon mentions of these motives in the Criminal Code of the Republic of Armenia. It is proposed that theft be considered complete when the owner or legal possessor of the property loses the actual ability to dispose of or use the property. Differences in the understanding of the concept of "dwelling" in substantive and procedural law create issues for law enforcement practice, so this concept should be defined solely in the Criminal Code, with the necessary amendments. Existing legal regulations should include among the qualified acts of robbery (brigandage) an aggravating circumstance of "negligence resulting in the death of a person or causing serious harm to health." To avoid repetitions, the legislative formulation of robbery should be changed to: “Robbery – open theft.” In one of the qualified types of theft, the term "from the object" is highly problematic, potentially leading to many interpretations and ambiguities. In this context, the norm should be clarified to state: “from another item held by the victim,” emphasizing that the item is directly with the victim, attached to their body or clothing. Part 1 of Article 255 of the Criminal Code should be rephrased to state: “Fraud – theft of property through deceit or abuse of trust, if the intent to steal the property arose beforehand, before the crime began.” Article 256 of the Criminal Code should also be edited to read: “Theft of property entrusted to the perpetrator, that is, transferred to their disposal, possession, or use, if the intent to steal the property arose after it was received lawfully.” The extremely controversial formulation “by actual or legally free will” should be excluded from the existing concept.